High Levels of Stress Due to the SARS-CoV-2 Pandemic among Parents of Children with and without Chronic Conditions across the USA - Miranda A.L. van Tilburg; Emily Edlynn; Marina Maddaloni; Klaas van Kempen; Maria Díaz-González de Ferris; Jody Thomas (MDPI AG, 2020)
Background: The 2020 SARS-CoV-2 pandemic led to community-wide measures affecting parents and children such as school/daycare closures, job losses, and interruptions in medical care for children with chronic diseases. This is the first study to describe the level of stress and mental health of parents of either healthy children or children with chronic conditions, during the 2020 pandemic. Methods: A representative sample of US parents was recruited from 10-17 April 2020. Parents completed online questionnaires about the past 7 days, including the Perceived Stress Scale, Resilient Coping Scale, Self-Efficacy Scale, Kansas Marital Satisfaction Scale, Parental Stress Scale, PROMIS Anxiety and Depression scales and various other pandemic-related stress questions Results: Levels of stressors (e.g., job loss, school closures, etc.) were high during this time (e.g., 79% of children attended home/online school) and parents reported being moderately to highly stressed. Rates of clinical anxiety (44.6%) and depression (42.2%) were high. Parents of children with chronic conditions reported higher levels of stress and worse mental health, but did not differ from other parents in dealing with stress or interruptions in work, child schooling, and marital satisfaction. Discussion: The COVID-19 pandemic has introduced unprecedented levels of stress for parents, especially those of children with chronic conditions. Mental health effects are expected to continue for months/years and preparation is needed to meet an increasing demand for mental health care.